Dark-field imaging in coronary atherosclerosis. Issue 94 (September 2017) - Hetterich, Holger; Webber, Nicole; Willner, Marian; Herzen, Julia; Birnbacher, Lorenz; Auweter, Sigrid; Schüller, Ulrich; Bamberg, Fabian; Notohamiprodjo, Susan; Bartsch, Harald; Wolf, Johannes; Marschner, Mathias; et al.
Highlights: Dark-field imaging is very sensitive for microcalcifications of coronary plaques. Dark-field is higher than attenuation signal intensity for microcalcifications. Simulations suggest that these findings can be transferred to clinical CT-scanners. Abstract: Objectives: Dark-field imaging based on small angle X-ray scattering has been shown to be highly sensitive for microcalcifications, e.g. in breast tissue. We hypothesized (i) that high signal areas in dark-field imaging of atherosclerotic plaque are associated with microcalcifications and (ii) that dark-field imaging is more sensitive for microcalcifications than attenuation-based imaging. Methods: Fifteen coronary artery specimens were examined at an experimental set-up consisting of X-ray tube (40 kV), grating-interferometer and detector. Tomographic dark-field-, attenuation-, and phase-contrast data were simultaneously acquired. Histopathology served as standard of reference. To explore the potential of dark field imaging in a full-body CT system, simulations were carried out with spherical calcifications of different sizes to simulate small and intermediate microcalcifications. Results: Microcalcifications were present in 10/10 (100%) cross-sections with high dark-field signal and without evidence of calcifications in attenuation- or phase contrast. In positive controls with high signal areas in all three modalities, 10/10 (100%) cross-sections showed macrocalcifications. In negative controls without high signal areas, no calcifications were detected. Simulations showed that the microcalcifications generate substantially higher dark-field than attenuation signal. Conclusions: Dark-field imaging is highly sensitive for microcalcifications in coronary atherosclerotic plaque and might provide complementary information in the assessment of plaque instability.